KOMPETENSI PROFESIONAL GURU PAI DALAM PENINGKATAN KUALITAS PELAKSANAAN EVALUASI PEMBELAJARAN - Fitri (UNISAN JURNAL, 2024)
This examination means to break down the job of educator proficient capability in further developing learning adequacy at MTs Amanah Ruteng, Manggarai Regime. The exploration strategy utilized is a subjective technique with a contextual investigation approach. Information assortment was helped out through participatory perception, top to bottom meetings with instructors, and examination of records connected with the educational plan and learning exercises at school. The examination results show that educator proficient skill plays a critical part in expanding the viability of learning at MTs Amanah Ruteng, Manggarai Regime. Educators who have great expert skill can get ready and carry out learning plans that are applicable to understudy needs. They are likewise ready to utilize a wide range of learning procedures as indicated by understudy learning styles and class qualities. What's more, expertly capable instructors can establish a helpful learning climate, inspire understudies, and give useful criticism to work on understudies' comprehension and learning accomplishment. In any case, the examination additionally tracked down a few difficulties in working on the expert skill of educators at MTs Amanah Ruteng, Manggarai Regime, like restricted assets and satisfactory help, as well as changes in instructive strategies that could influence educational program execution and learning in schools. This examination has significant ramifications for working on the nature of learning at MTs Amanah Ruteng, Manggarai Rule and different schools. Persistent endeavors are expected to foster educators' expert ability through efficient preparation, backing and training. Aside from that, there should be support from schools, government and society in establishing a climate that supports expanding educator proficient skill to accomplish ideal mastering viability.